Performance Analysis of BAZNAS Tapanuli Selatan District - Nauli, Mutiara; Batubara, Sarmiana; Batubara, Damri (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2022)
This study aims to analyze the performance of BAZNAS in South Tapanuli Regency in optimizing the collection, distribution, and utilization of zakat. The research method uses a descriptive qualitative approach with data collection techniques using interview and observation techniques. The subjects in this study were BAZNAS administrators in South Tapanuli Regency. The results of this study indicate that the performance of zakat collection, BAZNAS South Tapanuli Regency has two strategies, namely a socialization strategy by making a decree Zakat Management Unit to collect zakat among the community and an appeal strategy by making an appeal to coordinate with the treasurer of each Regional Apparatus Organization (OPD) to distribute professional zakat to BAZNAS. In the performance of zakat distribution, BAZNAS South Tapanuli Regency distributes zakat in two forms, namely consumptive zakat and productive zakat. In the performance of zakat utilization, BAZNAS South Tapanuli Regencyempowering productive zakat, namely providing business capital assistance in the form of revolving fund loans. Revolving fund loans are given to MSME group mustahik and fostered farmer groups.Keywords: Performance, Optimization, BAZNAS